Analisis Nilai Tambah pada Produk Koffie Hideung (Studi Kasus di CV Toean Koffie) - Wanda Alifah Mutiara Salsabila; Abubakar Abubakar; Luthfi Nur'azkiya (Program Studi Agribisnis, Fakultas Pertanian, Universitas Singaperbangsa Karawang, 2023)
CV Toean Koffie is one of the companies that runs a business in the coffee processing industry. The company utilizes coffee produced by farmers in Medal Sari Village to increase the economic value and price of coffee itself. The purpose of this study is to determine the coffee processing process, analyze the income, profit and added value obtained from the processing of Koffie Hideung, namely coffee beans into sachet coffee and premium coffee. The research was conducted at CV Toean Koffie from April-July 2022. The respondents to the study were workers at CV Toean Koffie. Sampling using purposive sampling. The sample used 1 processing industry with a sample number of 8 out of 10 workers on CV Toean Koffie. The analytical tools used are revenue analysis, profit analysis and value-added analysis using the Hayami method. The method of data collection is an interview based on questionnaires, observations, and documentation. Based on the results of the study, the processing activities at CV Toean Koffie include sorting, roasting, cooling, grinding, mixing coffee-sugar grounds, packaging, and storage. The total cost incurred by the company for processing Koffie Hideung amounted to Rp. 43,715,952.79, resulting in revenue of Rp. 62,872,445.68, and a total profit of Rp. 19,156,492.89. So that it can be said to be feasible and profitable. All Koffie Hideung (robusta) products provide added value. Coffee sachets are classified as medium added value with a ratio of 39.68%. Meanwhile, premium coffee products are classified as high added value, which is >40%. The conclusion from the research results that Koffie Hideung products have added value and are profitable.